Unobtrusive indicators of culture for organizations: a systematic review. Issue 5 (2nd September 2020) - Reader, Tom W; Gillespie, Alex; Hald, Julie; Patterson, Megan
ABSTRACT: We systematically reviewed the literature using unobtrusive measures to study organizational culture. To synthesize, theorize, and evaluate this research, we introduce the concept of an unobtrusive indicator of culture (UIC) for organizations. A UIC measures organizational culture through collecting data without engaging employees, and is conceptualized in terms of cultural artefacts. We identified thirty-five articles, containing 135 distinct UICs, drawn from 16 distinct data sources. UICs coalesced into two groups. First, textual UICs, with culture measured through language patterns in annual reports, employee online reviews, and emails. Second, UICs focusing on organizational practices, for instance, organizational policies or executive rewards. Over two-thirds (68%) of UICs measured values for integrity, results orientation, and clan cultures, and we conjecture that UICs may be most useful for studying aspects of culture sensitive to reporting biases, and benchmarking large samples of organizations. Forty-eight percent of UICs had good or promising construct validity: many were textual UICs, and those focusing on organizational practices were less established. UICs can potentially advance the study of organizational culture, yet must be developed and applied cautiously, with careful consideration of their advantages and limitations, and how they complement existing measurements and conceptualizations of culture.